2012
DOI: 10.1007/s11207-012-0110-x
|View full text |Cite
|
Sign up to set email alerts
|

Studying Sun–Planet Connections Using the Heliophysics Integrated Observatory (HELIO)

Abstract: The Heliophysics Integrated Observatory (HELIO) is a software infrastructure involving a collection of web services, heliospheric data sources (e.g., solar, planetary, etc.), and event catalogues -all of which are accessible through a unified front end. In this paper we use the HELIO infrastructure to perform three case studies based on solar events that propagate through the heliosphere. These include a coronal mass ejection that intersects both Earth and Mars, a solar energetic particle event that crosses th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The HELiophysics Integrated Observatory (HELIO) ‡ has compiled a list of web services which allows scientists to query and discover data throughout the heliosphere, from solar and magnetospheric data to planetary and inter-planetary data (Pérez-Suárez et al, 2012). HELIO is built with a Service-Oriented Architecture, i.e., its capabilities are divided into a number of tasks that are implemented as separate services.…”
Section: Heliomentioning
confidence: 99%
“…The HELiophysics Integrated Observatory (HELIO) ‡ has compiled a list of web services which allows scientists to query and discover data throughout the heliosphere, from solar and magnetospheric data to planetary and inter-planetary data (Pérez-Suárez et al, 2012). HELIO is built with a Service-Oriented Architecture, i.e., its capabilities are divided into a number of tasks that are implemented as separate services.…”
Section: Heliomentioning
confidence: 99%
“…The uncertainty is compensated for by expanding the search volume and lengthening the search time-slot; in effect, this is attaching an estimate of error to the spacetime location that the propagation model itself produces. The Solar-Heliospheric Event Ballistic Algorithm (SHEBA) [19] has been developed within HELIO as a first approximation to solve the propagation problem. This algorithm, built on top of HELIO services, offers three different propagation modes (i.e., CMEs, SIRs and high energetic particles) through a simple 2D ballistic propagation model [20].…”
Section: Event Propagationmentioning
confidence: 99%
“…SHEBA allows to run the propagation in two directions, from the Sun outwards into the heliosphere, and from any object (planet or spacecraft) backwards to the Sun. Though SHEBA is a basic propagation model, it has shown satisfactory results for noncomplex events (e.g., an individual CME propagating in a quiet environment) [19].…”
Section: Event Propagationmentioning
confidence: 99%
“…SHEBA is not data driven and it uses a simple ballistic model, i.e., all the propagation is done assuming a constant speed, though this approximation could seem very inaccurate, it has been shown that it is not far from reality during quiet periods [13]. The main aim in SHEBA was to offer a fast and easy propagation model to the users of HELIO.…”
Section: Propagation Models In Heliophysicsmentioning
confidence: 99%
“…The HELIO project [4,7,8,14] has developed SHEBA [13], a Propagation Model of the ballistic kind. Depending on whether it is run from the Sun to the planets or vice-versa and on which phenomena is investigated, SHEBA requires information on a variety of parameters such as the position on the surface on the Sun from where the event originates, its time and its expected speed at the source.…”
Section: Introductionmentioning
confidence: 99%